Tourism Development Through Collaborative Governance: Insights from Tegal Malaka Hill, Garut - Iriany, Ieke Sartika; Razzaq, Muhammad Akmal; Karmila, Mila; Pasciana, Rostiena (Future Science, 2025)
This study aims to analyze the strategy of Collaborative Governance in the development of Bukit Tegal Malaka tourist attraction in Garut Regency, employing a qualitative descriptive method through interviews, observations, and document studies. Referring to the model of Ansell and Gash (2008), the findings indicate that tourism development is driven by active community participation, institutional support through Village Regulations, and initial synergy with the Village-Owned Enterprise (BUMDes). However, the implementation still faces challenges such as low tourism awareness, limited access to capital, and insufficient support from local government. Nevertheless, the community-based initiative has generated both economic and social benefits for local residents, suggesting that Collaborative Governance has the potential to serve as an effective model of tourism governance when supported by capacity building, regulatory reinforcement, and the active involvement of all stakeholders.